A direct wavepath-based element localization algorithm to enable flexible ultrasound array imaging - Willey, C.L.; Chen, V.W.; Juhl, A.T. (Ultrasonics, 2024)
An algorithm is developed for determining the element locations of a flexible ultrasonic array when applied to a surface of unknown geometry. The algorithm forms a dataset of traveltimes from the direct wavepaths (i.e. rays) between transmitters and receivers, which serves as the input to an optimization scheme that iterates on the array element locations until an objective function is minimized. Once, the relative array locations have been determined, they are used as an input to a phased array ultrasound imaging algorithm. In this study, the total focusing method with full matrix capture is used as a testbed code to demonstrate the benefits of the relative array element localization algorithm. The algorithm is verified by simulation and experimentation. •A method for optimization-based detection of flexible ultrasound array element locations.•Experimental demonstration of method on structurally and biologically relevant materials.•Analysis of image blur as a function of errors in array element location estimates.